Comparative studies on single-layer reduced graphene oxide films obtained by electrochemical reduction and hydrazine vapor reduction - Wang, Zhijuan (2013)
The comparison between two kinds of single-layer reduced graphene oxide (rGO) sheets, obtained by reduction of graphene oxide (GO) with the electrochemical method and hydrazine vapor reduction, referred to as E-rGO and C-rGO, respectively, is systematically studied. Although there is no morphology difference between the E-rGO and C-rGO films adsorbed on solid substrates observed by AFM, the reduction process to obtain the E-rGO and C-rGO films is quite different. In the hydrazine vapor reduction, the nitrogen element is incorporated into the obtained C-rGO film, while no additional element is introduced to the E-rGO film during the electrochemical reduction. Moreover, Raman spectra show that the electrochemical method is more effective than the hydrazine vapor reduction method to reduce the GO films. In addition, E-rGO shows better electrocatalysis towards dopamine than does C-rGO. This study is helpful for researchers to understand these two different reduction methods and choose a suitable one to reduce GO based on their experimental requirements.